An integrated system framework of building information modelling and geographical information system for utility tunnel maintenance management. (September 2018) - Lee, Pin-Chan; Wang, Yiheng; Lo, Tzu-Ping; Long, Danbing
Highlights: A method that enables the integration of data required for maintenance management in BIM and 3D GIS environment. Monitoring data and related maintenance information are linked in the maintenance management system. A process to extend visualization functions of current computerized maintenance management system. A framework of a system to support utility tunnel maintenance management. Abstract: Utility tunnel should be well maintained for it services public pipelines and city operation. In the recent time, utility tunnel has been operated via computer maintenance management systems (CMMS) or building automation systems (BAS). However, CMMS or BAS lack of convenient visualization and interoperability. This paper aims to propose an integrated system of building information modelling (BIM) and geographic information system (GIS) to improve the performance of current maintenance management system. A system framework of BIM-3DGIS is proposed and required maintenance management functions are also developed based on practice demands. A real case of utility tunnel is used to demonstrate the system. Two scenarios and a questionnaire survey are conducted to validate the applicability and practicability. Results show that the proposed BIM-3DGIS system can ensure effective maintenance works and have well potential applications.